Steel plate-UHPC composite strengthening method for large-span prestressed concrete box girder bridges: Simulation, optimization, and case study - Tao Sun; Weikun He; Chengjun Tan; Jiahe An; Junde Hu; Lizhi Lu; Hua Zhao (Engineering Structures, 2026)

Influence of interface geometry on interfacial shear between precast UHPC and cast-in-place normal-strength concrete: Experimental and analytical investigation - Lei Tu; Weikun He; Hua Zhao; Chengjun Tan; Jiahe An; Junde Hu; Lizhi Lu (Engineering Structures, 2026)

An interpretable deep learning framework for UHPC dry joint shear strength prediction under small sample regimes - Jingqi Cao; Weikun He; Chengjun Tan; Lei Tu; Suiwen Wu; Jiahe An; Junde Hu; Hua Zhao (Engineering Structures, 2026)

Decadal nutrient addition reveals phosphorus limitation and its adaptive mechanisms in tropical rainforests - Qingshui Yu; Mark A. Anthony; Arthur Gessler; Xiangping Tan; Jiangling Zhu; Chengjun Ji; Zhiyao Tang; Jingyun Fang (Soil Biology and Biochemistry, 2025)

Explore the application potential of nanoporous material-based membrane separation technology in the energy sector - Chengjun Tan; Shuyu Wu; Mengna Weng; Jialiang Xian; Zixia Chen; Yutong Qi; Jiantang Zhang; Jun Chen; Huaben Bo (Journal of Environmental Chemical Engineering, 2025)

Orthotropic steel deck reinforcement technique for super-long span bridges with thin dense-reinforced UHPC Layers - Zihao Luo; Chengjun Tan; Junhui Cao; Kun Liu; Sui Luo; Jiahe An; Hua Zhao; Xudong Shao; Dutao Yi (Engineering Structures, 2025)

Experimental and numerical investigation on deck system of a 102 m simply supported prestressed UHPC box-girder highway bridge - Sui Luo; Hua Zhao; Dongqin Qiao; Chengjun Tan; Xudong Shao; Jing Ma; Huangguo Qian; Zhilian Liao; Zhentao Hu; Cuizhu Zhou (Engineering Structures, 2024)

Shear behavior on PBL shear connector with a relatively thin perforated steel plate in steel-UHPC composite bridge deck system - Zihao Luo; Hua Zhao; Dongqin Qiao; Yufei Zhang; Jiahe An; Chengjun Tan; Linong Liang; Anxing Liu; Xudong Shao (Engineering Structures, 2024)

Concept and flexural performance of non-prestressed steel plate-UHPC-NC composite girder bridge - Lei Tu; Hua Zhao; Dongqin Qiao; Junde Hu; Chengjun Tan; Jing Ma; Zhentao Hu; Huiren Qiu; Xudong Shao (Engineering Structures, 2024)

Au doped metal organic frameworks as di-functional photocatalysts for clearing organics in wastewater - Donglin Han; Juntao Niu; Yuchen Yang; Chengjun Huang; Wenguang Tan; XuanYi Zhang (Chemosphere, 2024)

Dynamic response of the inhomogeneous pavement structure containing a buried fault zone under the moving aircraft loads - Jiawei Wan; Bin Li; Yang Gao; Chengxuan Tan; Chengjun Feng; Peng Zhang (Bulletin of Engineering Geology and the Environment, 2022)

Characteristics and main causes of earth fissures in northeastern Beijing Plain, China - Jiawei Wan; Bin Li; Chengxuan Tan; Chengjun Feng; Peng Zhang; Bangshen Qi (Bulletin of Engineering Geology and the Environment, 2020)

Co-seismic and post-seismic effects of the Tohoku-Oki M W 9.0 earthquake in North and Northeast China - Chengjun Feng; Peng Zhang; Chengxuan Tan; Bangshen Qi; Lianjie Wang (Journal of Seismology, 2016)

Molecular structure of glycogen in diabetic liver - Bin Deng; Mitchell A. Sullivan; Jialun Li; Xinle Tan; Chengjun Zhu; Benjamin L. Schulz; Robert G. Gilbert (Glycoconjugate Journal, 2015)

The stress state of the Beichuan-Jiangyou segment of the Longmenshan fault before and after the Wenchuan M S 8.0 Earthquake - Chengjun Feng; Qunce Chen; Chengxuan Tan; Xianghui Qin; Peng Zhang; Wen Meng (Journal of Earth Science, 2014)

Crustal stress state and seismic hazard along southwest segment of the Longmenshan thrust belt after Wenchuan Earthquake - Xianghui Qin; Chengxuan Tan; Qunce Chen; Manlu Wu; Chengjun Feng (Journal of Earth Science, 2014)

Changes in topsoil carbon stock in the Tibetan grasslands between the 1980s and 2004 - YUANHE YANG; JINGYUN FANG; PETE SMITH; YANHONG TANG; ANPING CHEN; CHENGJUN JI; HUIFENG HU; SHENG RAO; KUN TAN; JIN‐SHENG HE (Global Change Biology, 2009)
Climate warming is likely inducing carbon loss from soils of northern ecosystems, but little evidence comes from large‐scale observations. Here we used data from a repeated soil survey and remote sensing vegetation index to explore changes in soil organic carbon (SOC) stock on the Tibetan Plateau during the past two decades. Our results showed that SOC stock in the top 30 cm depth in alpine grasslands on the plateau amounted to 4.4 Pg C (1 Pg=10 15 g), with an overall average of 3.9 kg C m −2 . SOC changes during 1980s–2004 were estimated at −0.6 g C m −2 yr −1 , ranging from −36.5 to 35.8 g C m −2 yr −1 at 95% confidence, indicating that SOC stock in the Tibetan alpine grasslands remained relatively stable over the sampling periods. Our findings are nonconsistent with previous reports of loss of soil C in grassland ecosystems due to the accelerated decomposition with warming. In the case of the alpine grasslands on the Tibetan Plateau studied here, we speculate that increased rates of decomposition as soils warmed during the last two decades may have been compensated by increased soil C inputs due to increased grass productivity. These results suggest that soil C stock in terrestrial ecosystems may respond differently to climate change depending on ecosystem type, regional climate pattern, and intensity of human disturbance.